2011
DOI: 10.1249/mss.0b013e31821f5d4e
|View full text |Cite
|
Sign up to set email alerts
|

Startup Circuit Training Program Reduces Metabolic Risk in Latino Adolescents

Abstract: Purpose This study aimed to test the effects of a circuit training (CT; aerobic + strength training) program, with and without motivational interviewing (MI) behavioral therapy, on reducing adiposity and type 2 diabetes risk factors in Latina teenagers. Methods Thirty-eight Latina adolescents (15.8 ± 1.1 yr) who are overweight/obese were randomly assigned to control (C; n = 12), CT (n = 14), or CT + MI (n = 12). The CT classes were held twice a week (60–90 min) for 16 wk. The CT + MI group also received indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
113
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(126 citation statements)
references
References 37 publications
3
113
1
6
Order By: Relevance
“…(93,95) Therefore the validity of lumbar spine BMD results can be questionable, highlighting the greater reliance on total hip BMD measures for the estimation of fracture risk. (58,60,64,82,96) The majority of studies identified in this systematic review and meta-analysis investigated total body BMD, which was significantly reduced by 6-month (but not by 3-month or 12-month) weight-loss interventions. However, measures of total body BMD are not clinically relevant because they do not identify specific areas that are affected by loss of bone mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(93,95) Therefore the validity of lumbar spine BMD results can be questionable, highlighting the greater reliance on total hip BMD measures for the estimation of fracture risk. (58,60,64,82,96) The majority of studies identified in this systematic review and meta-analysis investigated total body BMD, which was significantly reduced by 6-month (but not by 3-month or 12-month) weight-loss interventions. However, measures of total body BMD are not clinically relevant because they do not identify specific areas that are affected by loss of bone mass.…”
Section: Discussionmentioning
confidence: 99%
“…Although we were able to categorize interventions according to the levels of prescribed energy intake, this did not take into account differences in macronutrient composition of the diets. A further limitation of this metaanalysis was that only 25% of the included studies involved comparison with a control group, (22,25,36,40,(45)(46)(47)73,74,80,82) as mentioned in the second paragraph of this Discussion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a circuit training approach allowed sedentary overweight and obese adolescents to train at 70% to 85% of their maximum heart rate for 60 to 90 minutes by dividing their exercise training into 2-minute bouts followed by 1 minute of recovery between activities. 36 Davis et al 50 suggest training programs involving a combination of aerobic and resistance training can incorporate short aerobic intervals into circuit training and allow overweight and obese adolescents with low aerobic fitness to accumulate the required duration of aerobic exercise and improve adherence by incorporating smaller, more manageable exercise bouts.…”
Section: Discussionmentioning
confidence: 99%
“…29 IR was calculated by using fasting levels of insulin and glucose by using the homeostasis model assessment (HOMA) technique in each study included in this analysis. 22,25,31,32,[34][35][36][37][38][39][40][41] A decrease in fasting insulin levels or IR among participants in exercise interventions resulted in a positive ES. Two authors (M.V.F.…”
Section: Es Calculationmentioning
confidence: 99%
See 1 more Smart Citation